The Influence of Product Quality and Price on Purchasing Decisions - Ramlawati; Murniati, Sitti (Journal of Management Research and Studies, 2023)
This research is included in the type of explanatory research. This technique uses multiple regression analysis, where the technique will test the hypothesis that there is an influence between the independent variable and the dependent variable. Multiple regression analysis is an analysis of the relationship between one dependent variable and or more independent variables. The objects of this research are product quality, price, and purchasing decisions. The subject of this research is visitors who buy products at BINTANG Market. The types of data used are primary data in the form of questionnaires, and secondary data in the form of documentation information published by the company. The sampling technique used the Slovin formula, so that the sample in this study amounted to 80 respondents or BINTANG Market consumers. The data analysis technique in this study is descriptive statistical analysis, classical assumption test, and hypothesis testing. The results of this study indicate: 1) product quality has a significant effect on purchasing decisions; 2) price has a significant effect on purchasing decisions. 3) The Adjusted R Square value of 0.395 means that 39.5% of purchasing decisions are determined by product and price variables, while the other 60.5% is caused by other variables not examined.